Patterned Hippocampal Stimulation Facilitates Memory in Patients With a History of Head Impact and/or Brain Injury - Roeder, Brent M.; Riley, Mitchell R.; She, Xiwei; Dakos, Alexander S.; Robinson, Brian S.; Moore, Bryan J.; Couture, Daniel E.; Laxton, Adrian W.; Popli, Gautam; Munger Clary, Heidi M.; Sam, Maria; Heck, Christi; et al. (Frontiers in Human Neuroscience, 2022)
Rationale: Deep brain stimulation (DBS) of the hippocampus is proposed for treatment of memory deficits. Many pre-clinical DBS paradigms are addressed in epilepsy patients undergoing intracranial monitoring for seizure localization, since they already have electrodes implanted in brain areas of interest. Even though epilepsy is usually not the disorder targeted by DBS, the studies can nevertheless model other memory-impacting disorders, such as Traumatic Brain Injury. (TBI) Methods: Human patients undergoing Phase II invasive monitoring for intractable epilepsy were implanted with electrodes capable of recording neurophysiological signals. Subjects performed a delayed-match-to-sample (DMS) memory task while hippocampal ensembles from CA1 and CA3 cell layers were recorded to compute a multi-input, multi-output (MIMO) model of CA3-to-CA1 neural encoding, and a Memory Decoding Model (MDM) derivative of the MIMO model. After model generation, subjects again performed the DMS task while either MIMO-based or MDM-based patterned stimulation was delivered to CA1 electrode sites during the encoding phase of the DMS trials. Each subject were sorted (post-hoc) by prior experience of repeated and/or mild-to-moderate brain injury (RMBI), traumatic brain injury (TBI), or no history (control) and scored for percentage successful Delayed Recognition (DR) recall on stimulated vs nonstimulated DMS trials.. The subject’s medical history was unknown to the experimenters until after individual subject memory retention results were scored. Results: When examined compared to control subjects, both TBI and RMBI subjects showed increased memory retention in response to both MIMO and MDM-based hippocampal stimulation. Furthermore, effects of stimulation were also greater in subjects who were evaluated as having pre-existing mild-to-moderate memory impairment. Conclusion: These results show that hippocampal stimulation for memory facilitation was more beneficial for subjects who had previously suffered a brain injury (other than epilepsy), compared to control (epilepsy) subjects who had not suffered a brain injury. This study demonstrates that the epilepsy/intracranial recording model can be extended to test the ability of DBS to restore memory function in subjects who previously suffered a brain injury other than epilepsy, and support further investigation into the beneficial effect of DBS in TBI patients.